2022
DOI: 10.3390/curroncol29050247
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors in Cancer Therapy

Abstract: The discovery of immune checkpoint proteins such as PD-1/PDL-1 and CTLA-4 represents a significant breakthrough in the field of cancer immunotherapy. Therefore, humanized monoclonal antibodies, targeting these immune checkpoint proteins have been utilized successfully in patients with metastatic melanoma, renal cell carcinoma, head and neck cancers and non-small lung cancer. The US FDA has successfully approved three different categories of immune checkpoint inhibitors (ICIs) such as PD-1 inhibitors (Nivolumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
214
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 573 publications
(348 citation statements)
references
References 148 publications
0
214
0
1
Order By: Relevance
“…To date the ICIs approved by the FDA include blocking antibodies targeting cytotoxic T-lymphocyte protein 4 (CTLA-4) (ipilimumab) and programmed cell death protein 1 (PD-1) (pembrolizumab, nivolumab, cemiplimab, dostarlimab) and its ligand PD-L1 (atezolizumab, avelumab, durvalumab) [9]. However, several other antibody ICIs have been approved by other agencies eg the anti-PD-1 antibodies sintilimab, camrelizumab and zimberelimab [10] (https:// clini caltr ials.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…To date the ICIs approved by the FDA include blocking antibodies targeting cytotoxic T-lymphocyte protein 4 (CTLA-4) (ipilimumab) and programmed cell death protein 1 (PD-1) (pembrolizumab, nivolumab, cemiplimab, dostarlimab) and its ligand PD-L1 (atezolizumab, avelumab, durvalumab) [9]. However, several other antibody ICIs have been approved by other agencies eg the anti-PD-1 antibodies sintilimab, camrelizumab and zimberelimab [10] (https:// clini caltr ials.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…Many trials have focused on antibodies blocking PD-1/PD-L1 and CTLA-4 as single agents or in combinations in B-NHL patients ( 134 ). Ipilimumab is an anti-CTLA-4 antibody that is approved to treat metastatic melanoma and several other tumor types ( 135 ). Studies in patients with solid tumors indicated that ipilimumab treatment depleted intratumoral Tregs possibly through antibody-dependent cell mediated cytotoxicity ( 136 ).…”
Section: Impact Of Targeted Therapiesmentioning
confidence: 99%
“…In the analysis of immune checkpoint gene expression in the HRisk and LRisk groups, we found that PDL-1 was highly expressed in the HRisk group, and that highly expressed PDL-1 could inhibit the migration and proliferation of T cells by binding to PD-1 of T cells, thus inducing tumour tolerance and T-cell failure. Anti-PD-1 could significantly reverse this process to restore the anticancer function of T cells ( 42 ); therefore, the HRisk group was more sensitive to anti-PD-1 treatment. The above results suggest that treatment with paclitaxel combined with anti-PD-1 in the HRisk group may lead to better therapeutic outcomes.…”
Section: Discussionmentioning
confidence: 99%